Breed effects and heterosis on milk yield in Murrah buffaloes x Mediterranean - Ramirez-Diaz, J. [UNESP]; Olivera, J. A. [UNESP]; Mourão, G. B.; Tonhati, H. [UNESP] (My University, 2010)
The objective of this study was to evaluate the occurrence of differences between genetic groups of buffaloes for milk production traits, as total milk yield (TM/kg), protein (Prot/kg), fat (Fat/Kg), lactose (Lact/kg) and total solids (TS/kg), and estimate from them heterosis for TM/kg. To this aim, we used 609 observations belonging to 248 lactations of Murrah (Mu) and Mediterranean buffaloes in the different breed proportions, 1/2Murrah + 1/2Mediterranean (1/2Mu1/2Me) and 3/4Murrah x 1/4 Mediterranean (3/4Mu1/4Me) of from the Rio Pardo's farm, localized in Bocaina city (SP-Brazil). The variance analysis were performed by the methodology of mixed models, considering as fixed effects genetic group and the contemporary groups, constituted for year. The calving age of dams (linear and quadratic effects) and the lactation length (linear effect) was considering as covariates of the model. The animal was considering as random effects. The genetic group had a significant effect (P<0,05) for all traits, except Lac/kg. The mean value for MT/kg were 1947 ± 23.268kg; 2157.4 ± 45.6kg; 2078.6 ± 73.9kg and 2015 ± 63.8kg for Mu, 1/2Mu1/2Me, 3/4Mu1/4Me and Me buffaloes respectively, differences were not statistically significant, except between the means of animals Mu and 1/2Mu1/2Me (P<0.05). For the constituents of milk, the estimated average protein, fat and total solids were, respectively, equal to 85.0±1.8Kg, 124.4±3.4Kg and 331.4±6.9kg for Mu 97.4±2.9Kg, 139 .9±5.3kg e 347.7±6.9kg for 1/2 Mu1/2Me (F1); 98.7±5.9kg, 123.7±10.9kg and 374.6±22.1kg for 3/4Mu1/4Me; e 97.6±4.7kg, 148.1±8.5kg e379.9±17.4kg for Me buffaloes. The estimative of heterosis in F1 (1/2Mu1/2Me) was 8.9% to TM/kg, while for animals 3/4Mu1/4Me was 4.9%. These results shows that the group F1 with the maximum expected heterosis (100%) has the highest TM/kg, according to the assumption that increasing heterozygosity lead to augment heterosis, whilst the retention of heterosis in animals 3/4Mu1/4Me is 50%. It should be noted, however, that further studies on the performance of crossbred animals are needed, considering, particularly a greater number of observation, beyond the effect of addition of breed.
Keywords: Bred; Heterosis; Mediterranean; Murrah